(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Study on physical measurements of human body is anthropometry. Apart from anthropology research, forensic aspects of anthropometry deal with personal identification in criminal investigation. Forensic studies on foot prints, iris, finger prints, cheiloscopy, bite marks have been well established in literature. However, external ear morphometry from adult human is an important topic of forensic research and is not well documented across different geographical barriers. Therefore,present study deals with ear morphometry of 100 adultsfrom east India with an aim of sexual Total ear length (TEL) , ear length above tragus (ELAT) , ear length below tragus (ELBT), concha length (CL) and concha breadth (CB) . Both right and left ears were taken into considerations. Physical measurements were taken and statistically analysed. A discriminant function equation was obtained. Overall, 86.0% of original grouped cases were correctly classified. At the individual group level, 82% of male and 90% of female were correctly classified. Cross-validated results revealed 81% of samples were correctly classified by this model. The Wilk’s Lambda is 0.475, a good fit indicative for the predicted model.External ear morphometrics can be a useful forensic tool in sexual dimorphism. However, it varies among population and geographical barriers. The mathematical model may be used for East Indian population.